Special Issue on Advances in Deep Learning - Diego Gragnaniello; Andrea Bottino; Sandro Cumani; Wonjoon Kim (Applied Sciences, 2020)
Nowadays, deep learning is the fastest growing research field in machine learning and has a tremendous impact on a plethora of daily life applications, ranging from security and surveillance to autonomous driving, automatic indexing and retrieval of media content, text analysis, speech recognition, automatic translation, and many others [...]